The Effect Of Hardiness And Optimism On Career Adaptability In College Students - Syavira Nur Kamila; Nasywa Haraidha Surfia; Fatiyaturrahmah; Lucky Purwantini (Profesional Muda Cendekia Publishing, 2023)
This study aims to determine the influence of hardiness and optimism on career adaptability in college students. This research uses quantitative methods. The subjects in this study were 134 students from several universities in Indonesia. The sampling technique used in this study was a convenience sampling technique, namely those found by the researcher and deemed suitable as a sample, and willing to follow research by having data in accordance with the criteria made by researchers. Data collection in this study used three scales, namely the career adaptability scale, the hardiness personality scale and the optimism scale made by the researcher. The career adaptability scale consists of 21 items with a reliability coefficient of 0.702. The hardiness scale consists of 20 items with a reliability coefficient of 0.904. The optimism scale consists of 12 items with a reliability coefficient of 0.882. Data analysis techniques in this study were multiple linear regression tests and simple correlation tests. The results of the hypothesis analysis show that there is an influence between hardiness and optimism on career adaptability of 47.8% with R Square 0.478, F 60.019. With p 0.000 (p <0.05), so the hypothesis is accepted.